Genetic diversity analysis of some local biodiesel plant (Jatropha curcas L.) in Bangladesh: Genetic diversity analysis of Jatropha curcas L in Bangladesh - Khatun, Fahmida; Rahman, Md Mahfuzur; Habib, Md Ahasun; Haque, Md Shahidul; Rashid, Harun-or; Saha, Sumitra; Rahman, Arrafy (Journal of the Bangladesh Agricultural University, 2019)
The present study was conducted to analyze genetic diversity among biodiesel producing plant Jatropha curcas genotypes using six RAPD primers. The J. curcas samples were collected from ten agro climatic regions in Bangladesh. The six primers produced 31 DNA bands. All the DNA bands (31) showed 100% polymorphism. Overall gene frequency of 10 genotypes of J. curcas was ranged from 0.10 to 0.90. The average Nei’s gene diversity and Shannon’s Information Index for all loci were estimated 0.2994 and 0.4650, respectively. The gene diversity value was ranged from 0.18 to 0.50 and Shannon’s Information Index was ranged from 0.3251 to 0.6931. Inter-germplasm similarity indices (Si) ranged from 5.56 to 66.67% with an average of 33.906%. The similarity coefficient range varied from 0.00 to 0.971. The UPGMA dendogram constructed from Nei’s (1972) genetic distance group indicated segregation of the ten J. curcas germplasms into three main clusters. Cluster I, II and III possessed 8, 1 and 1 germplasms, respectively. This study revealed that at least three different J. curcas genotypes are available in Bangladesh. The RAPD technique is, however, found to be useful in studying genetic variation among J. curcas genotypes of different regions in Bangladesh. <!–StartFragment –> J Bangladesh Agril Univ 17(4): 437–445, 2019